1999
DOI: 10.1007/s002340050786
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral mesial temporal sclerosis: MRI with high-resolution fast spin-echo and fluid-attenuated inversion-recovery sequences

Abstract: We report a retrospective analysis of MRI in 206 patients with intractable seizures and describe the findings in bilateral mesial temporal sclerosis (MTS) on fast spin-echo (FSE) and fast fluid-attenuated inversion-recovery (fFLAIR) sequences. Criteria for MTS were atrophy, signal change and loss of the digitations of the head of the hippocampus. In patients with bilateral MRI signs of MTS, correlation with clinical electro, volumetric MRI data and neuropsychological tests, when available, was performed. Bilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Most patients present with complex partial seizure. Bilateral involvement is seen in 10% [7]. Classic MRI findings include volume loss and an abnormal increased T 2 and FLAIR signal of the hippocampus as a result of underlying gliosis (Figure 4a) and the subsequent increase in free water content.…”
Section: Epilepsy Syndromementioning
confidence: 99%
“…Most patients present with complex partial seizure. Bilateral involvement is seen in 10% [7]. Classic MRI findings include volume loss and an abnormal increased T 2 and FLAIR signal of the hippocampus as a result of underlying gliosis (Figure 4a) and the subsequent increase in free water content.…”
Section: Epilepsy Syndromementioning
confidence: 99%
“…We retrospectively reviewed 27 FP lesions (for both readers) and found that most (77.8%) showed loss of internal structure in a single slice but were normal in successive slices, which diminished the specificity for TLE. Since additional findings, including atrophy, T2 signal intensity abnormalities, and loss of digitations of the hippocampal head, are frequently detected in hippocampal sclerosis [ 29 30 ], a single finding of loss of internal structure in a single slice should be cautiously interpreted.…”
Section: Discussionmentioning
confidence: 99%
“…In these instances, other regions of archicortex, such as paralimbic cortex or insula, should serve as internal reference. Identification of bilateral pathology will have important treatment consequences, for example, bilateral MTS may preclude surgical resection in many cases 38,39 …”
Section: Hippocampal Digitationsmentioning
confidence: 99%